Wspólnotowe społeczeństwa a wzrost gospodarczy : mechanizmy oddziaływania - Maziarz, Mariusz (Wydawnictwo Uniwersytetu Wrocławskiego, 2016)
Recent econometric research showed that there is a positive correlation between collectivism of a society and economic development. In this article, I aim at analyzing the causal mechanisms that connect this dimension of culture and economic efficiency. On the base of the conducted meta-analysis of questionnaires, case studies and other empirical research, I coined the following four possible causal mechanisms that make economies of collectivist-oriented societies grow faster: (1) more efficient business relations among economic agents; (2) rarer egoistic behaviours; (3) increased security due to belonging to a group and (4) positive influence on innovativeness
Keywords: kolektywizm; indywidualizm; rozwój gospodarczy; mechanizm przyczynowy